Enhancing Neural Activation in Older Adults: Action Observation-Primed Swallowing Imagery Reveals Age-Related Connectivity Patterns - Hao Xiong; Jin-Jin Chen; Meng-Huan Wang; Lu Zhang; Feng Lin (IEEE Transactions on Neural Systems and Rehabilitation Engineering)
Aging-related swallowing decline, known as presbyphagia, significantly increases the risk of dysphagia and aspiration pneumonia in older adults. Enhancing cortical activation and functional connectivity through non-invasive methods is crucial for improving swallowing function. This study investigates the use of action observation (AO) as a priming method to enhance motor imagery (MI) for promoting swallowing-related cortical activity. A total of 22 healthy young adults and 20 healthy older adults were recruited. Participants completed two swallowing imagery tasks: an 8-minute AO-primed task and an 8-minute unprimed task. Functional near-infrared spectroscopy was used to measure changes in oxyhemoglobin concentration as an indicator of cortical activation. Corrected imaginary phase-locking values (ciPLVs) were calculated to estimate functional connectivity between brain regions. In young adults, AO-primed tasks showed widespread bilateral activation in the sensorimotor cortex, supplementary motor area (SMA), and visual cortex, while unprimed tasks activated only the right inferior frontal gyrus. In older adults, AO-primed tasks activated the left sensorimotor cortex, SMA, and visual cortex, but unprimed tasks did not result in any significant cortical activation. Despite both age groups recruiting similar cortical networks, older adults exhibited reduced connectivity, particularly in the prefrontal-sensorimotor pathways during AO-primed tasks. AO-priming enhances cortical activation and connectivity in both young and older adults during swallowing imagery tasks. However, older adults demonstrate weaker neural connectivity, suggesting that age-related cortical decline may limit the effectiveness of such interventions. AO-primed MI may serve as a promising strategy for improving swallowing function in older populations.